Komunikasi interpersonal pramuwisata dalam memberikan informasi kepada wisatawan di kota palembang - Fildzah Bahirah Yuisman; Desy Misnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to explore how interpersonal communication is carried out by tour guides in providing information to tourists in Palembang City. The research uses a qualitative approach with data collection methods including in-depth interviews, observation, and documentation involving five informants, consisting of three tour guides and two tourists. This study applies George Herbert Mead’s Symbolic Interactionism theory, which includes the elements of Self, Mind, and Society. The findings indicate that the interpersonal communication conducted by tour guides not only serves to convey information but also functions to build social relationships with tourists. These interactions occur in various situations with local tourists, out-of-town visitors, and religious tour groups where differences in social background, age, and travel purpose influence the way communication takes place.